2
$\begingroup$

A CAS plot suggests that for $x\in[0,\pi/2]$:

$$\cos^2x\leq 2\, e^{-x^2/4}-1.$$

The difference is not increasing in this range so I don't think differentiation alone will do.

Any suggestions welcome.

Note $\cos x\leq e^{-x^2/2}$ in this range.

$\endgroup$
1
$\begingroup$

We can actually prove that

$$ 2e^{-x^2/4}-1\ge\cos x,\quad\forall x\in[0,\pi/2].\tag{1} $$

It is a tighter inequality because $\cos x\ge\cos^2x$ in the interval. We have $$ (1)\iff e^{-x^2/4}\ge \frac{1+\cos x}{2}=\cos^2(x/2)\quad\forall x\in[0,\pi/2].\tag{2} $$ Now denote $t=x/2\in[0,\pi/4]$ and continue $$ (2)\iff e^{-t^2}\ge\cos^2t\iff e^{-t^2/2}\ge\cos t,\quad\forall t\in[0,\pi/4].\tag{3} $$ The last inequality in (3) can be estimated from the Taylor expansions using at the second step that $|t|<1$, hence, $t^6\le t^4$ $$ e^{-t^2/2}\ge 1-\frac{t^2}{2}+\frac{t^4}{8}-\frac{t^6}{48}\ge 1-\frac{t^2}{2}+t^4\Big(\underbrace{\frac{1}{8}-\frac{1}{48}}_{=\frac{5}{48}>\frac{1}{24}}\Big)\ge 1-\frac{t^2}{2}+\frac{t^4}{24}\ge\cos t. $$


P.S. Explanations of inequalities from Taylor expansions with Lagrange remainders: \begin{eqnarray} e^{-x}&=&1-x+\frac{x^2}{2}-\frac{x^3}{3!}+\frac{e^{-\xi}}{4!}x^4\ge1-x+\frac{x^2}{2}-\frac{x^3}{3!},\\ \cos x&=&1-\frac{x^2}{2}+\frac{x^4}{4!}-\frac{\cos\xi}{6!}x^6\le1-\frac{x^2}{2}+\frac{x^4}{4!}. \end{eqnarray}


EDIT: Thanks to Marty Cohen sharing the link to a really elementary proof of (3) by differentiation.

$\endgroup$
  • 1
    $\begingroup$ How do you know that you can truncate the series? For some valid proofs, see math.stackexchange.com/questions/2769766/… $\endgroup$ – marty cohen Jun 7 '18 at 21:01
  • $\begingroup$ @martycohen Truncations can be validated by the fact that the Lagrange remainder is non-negative for $\exp$ and non-positive for $\cos$. $\endgroup$ – A.Γ. Jun 7 '18 at 21:03
  • $\begingroup$ Then it should be stated with a link to a proof. $\endgroup$ – marty cohen Jun 8 '18 at 2:31
2
$\begingroup$

The given inequality is a consequence of $$ f(x)=\frac{\sin^2 x}{x^2} > \frac{2-2e^{-x^2/4}}{x^2}=g(x) \tag{1}$$ for any $x\in\left(0,\frac{\pi}{2}\right)$. $(1)$ is a pretty loose inequality, and both $f(x)$ and $g(x)$ are decreasing and concave functions over $I=\left(0,\frac{\pi}{2}\right)$. In particular $$ \forall x\in I,\quad f(x)\geq 1-\frac{2}{\pi}\left(1-\frac{4}{\pi^2}\right)x>\begin{smallmatrix}\text{the equation of the tangent line}\\\text{to the graph of }g(x)\text{ at }x=\pi/2\end{smallmatrix}\geq g(x)\tag{2} $$ and $(1)$ is proved.

$\endgroup$
1
$\begingroup$

Hint. Split the interval $[0,\pi/2]$ in two halves.

1) Show that for $x\in [0,\pi/4]$, $$\cos^2(x)\leq 1-\frac{x^2}{2}\leq 2 e^{-x^2/4}-1.$$ Note that the Taylor expansions at $x=0$ of the two functions are $$\cos^2(x)=1-\frac{x^2}{2} +O(x^4)\quad\mbox{and}\quad 2 e^{-x^2/4}-1=1-x^2+O(x^4).$$

2) Show that for $x\in [\pi/4,\pi/2]$, $$\cos^2(x)\leq 1-\frac{2x}{\pi}\leq 2 e^{-x^2/4}-1.$$ Note that $\cos^2(x)$ is convex and $2 e^{-x^2/4}-1$ is concave in such interval.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.